TINJAUAN YURIDIS TERHADAP PERKAWINAN DI BAWAH UMUR BERDASARKAN UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN Jo UNDANG-UNDANG NOMOR 23 TAHUN 2002 TENTANG PERLINDUNGAN ANAK - Sixtriani, Mulia; Hanifah, Mardalena; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Underage marriage is a marriage practices performed by couples in which one or both old and young in view of the present. This happens because of the provisions of Article 7 paragraph (2) of Law No. 1 of 1974 on marriage that give space to each person to perform underage marriage, because in the article or in the explanation of the Act does not explain the reason for the important for a person to perform underage marriage. The practice of underage marriage is in need of attention and setting clear, because there are even more people in Indonesia to underage marriage. The purpose of this thesis, namely: First, to determine the setting of underage marriage by Act No. 1 of 1974 concerning marriage are in accordance with Act No. 23 of 2002 on the protection of children, Second, to determine the legal protection of children who do underage marriage according to Law No. 23 of 2002 on the protection of children.Keywords : underage marriage- legal protection-children